2009
DOI: 10.1002/er.1653
|View full text |Cite
|
Sign up to set email alerts
|

Life verification of large capacity Yardney Li-ion cells and batteries in support of NASA missions

Abstract: SUMMARYLithium-ion batteries have been used on a number of NASA missions and have been base-lined for use on a number of up-coming aerospace applications. The Li-ion cells and batteries that have been developed together with Yardney Technical Products are especially attractive due to their high specific energy and energy density, good performance over a wide operating temperature range, as well as their good calendar and cycle life performance. However, given that the Li-ion technology is relatively new to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Nevertheless, artificial neural networks (ANNs) present a useful alternative for forecasting nonlinear dynamics and complex behaviors [19][20][21][22][23][24][25][26]. ANN techniques are capable of solving complex problems where traditional methods have failed.…”
Section: Structure Of the Rnn-based Predictormentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, artificial neural networks (ANNs) present a useful alternative for forecasting nonlinear dynamics and complex behaviors [19][20][21][22][23][24][25][26]. ANN techniques are capable of solving complex problems where traditional methods have failed.…”
Section: Structure Of the Rnn-based Predictormentioning
confidence: 99%
“…In this study, cell temperature (T), the amplitude of SOC variations (DSOC = SOCmax À SOCmin), current pulse (I) magnitude, and the charge throughput of a micro-cycle (CT in As) are considered the main factors of aging in power cycling tests [21][22][23][24].…”
Section: Accelerated Aging Testsmentioning
confidence: 99%
“…From literature and previous studies on lithium-ion battery aging, it was demonstrated that, for power cycling aging, temperature (T), the State-of-Charge variation (∆SoC) and the magnitude of the current pulse (I) were considered as the main factors of aging [9]. However, for calendar aging, SOC and temperature are the main influencing parameters on battery performances [10].…”
Section: Combined Power-cycling/calendar Aging Experimentsmentioning
confidence: 99%
“…The rover could perform reconnaissance activities [12] to identify interesting targets and maps for future missions. After a long time, the rover may lose capabilities [28,42] (e.g. reduced mobility due to wear and tear on motors or mechanical systems, reduced power generation due to battery degradation, accumulated dust on solar arrays), as happened with the Spirit and Opportunity rovers.…”
Section: Planetary Mars Domain a Real-world Motivation Examplementioning
confidence: 99%